Yoruba movies and religious propagation in Yorubaland (2013)
Yoruba movies have made its debute and prominence from the stage plays, cinemas and celluloid stock during the colonial era. The influx of Yoruba movies encouraged some religious groups to manipulate these means to propagate their faith, while some of them turned it to tools of war meant to wield at will. Yoruba language is unique in its ability to express long words in a short form to promote wisdom and intelligence. Based on these facts, this paper addresses some pertinent features; on the relevance of religious belief to tile Yoruba, the relationship between the cultures and traditional drama in Yorubaland by focusing the three major religions in Nigeria with particular reference to Christian evangelism through Yoruba movie outlining how it has distorted Islamic values and maligned the image of the Muslims, which led to the analysis of Agbara Nla. This paper also sheds light on the Islamic accommodation of cultural values so long it does not go against its fundamental principles. It concludes by warning on the danger in using Muslim personalities to project bad characters in Yoruba movies and encourages the Yoruba artist to implement the use of Yoruba movies to facilitate unity among different religious groups in Yorubaland. If this warning is heeded it will promote peaceful coexistence among the different religious practitioners.